Introducing a New Emissions Certification Procedure for European Light-Duty Vehicles: Monte Carlo Simulation of the Potential Effect on Fleet Carbon Dioxide Emissions. Issue 1 (2016) - Tsiakmakis, Stefanos; Ciuffo, Biagio; Fontaras, Georgios; Anagnostopoulos, Konstantinos; Arcidiacono, Vincenzo; Praksova, Renata; Marotta, Alessandro
Initiatives to reduce carbon dioxide (CO2 ) emissions from light-duty vehicles have been the cornerstone of European policy for curbing greenhouse gas emissions from road transport in past decades. The political approach has shown its effectiveness in recent years. However, the use of an outdated test procedure to measure the progress in reducing fuel consumption and CO2 emissions jeopardizes these efforts. For this reason, the European Commission is committed to introducing, in the shortest possible time, the new Worldwide Harmonized Light Vehicles Test Procedure (WLTP), developed through the United Nations Economic Commission for Europe, to reduce the gap between type approval and real-world figures on CO2 emissions. The introduction, however, requires the adoption of the CO2 targets set by the relevant European regulations. The approach selected by the European Commission for dealing with this issue required the development of a technology-oriented vehicle simulation model, CO2 MPAS, which has been extensively validated against simulated and real data to demonstrate its capacity to capture the differences between the two certification procedures. In the present study, CO2 MPAS is used to analyze the possible effects of the introduction of WLTP in the European vehicle market in terms of reported CO2 emissions. An approach based on Monte Carlo sampling has been adopted because of the lack of detailed vehicle information. The differences in estimated CO2 emissions are compared and discussed. Results indicate the accuracy and robustness of CO2 MPAS in reproducing CO2 emissions at the fleet level. The results also indicate an increase in global CO2 emissions from existing passenger cars on the order of 10 g/km.